Como os bancos brasileiros ajustam suas razões de capital: uma análise do período de 2005 a 2010 - Brasil, Carolina Machado (2012)
Implementation of Basel, whose goal is to strengthen the soundness and stability of the financial system is essentially based on the stipulation of a minimum capital ratio. Although a higher ratio of capital increase costs for institutions, it is common to note that many of these institutions maintain a capital ratio above the regulatory minimum. Thus, this work is meant to examine how Brazilian banks adjust their capital ratios. Secondarily aims to assess the determinants of the speed of adjustment, emphasizing the importance of the variables of rating. For this purpose, we use the methodology employed by Berger et al. (2008) using a model in three stages. We used quarterly data from 2005 to 2010 refer to 57 banks. As a result it was found that if the bank has traded lower its rate of capital, the larger the size the greater the bank’s capital held, which is contrary to results obtained in the literature, and the proxies to measure the rating institutions were non-significant.